Profile of Physical Fitness of Young Football Players at SDN Cibeusi - Subashini Periasamy; Reni Farenia; Pintoko Tedjokusumo (Althea Medical Journal, 2015)
Background: Health-related physical fitness components are important in hypokinetic disease prevention and good sports performance. The aim of this research is to evaluate the physical fitness profile of the SDNCibeusi young football players based on Fitnessgram.Methods: This study was participated by 20 subjects ranging from 10 to 12 years old boys who played for the school football team in SDN Cibeusi. This descriptive study was conducted in the school field in the month of November 2012. Physical fitness components that were tested are aerobic capacity,V02 max using the one-mile run test, muscle endurance by performing push-up and curl-up test, flexibility using the flexometer and body composition by measuring the body mass index and fat fold measurement. The mean and standard deviation of the results were tabulated.Results: Aerobic capacity and percentage of body fat showed 100% of them scored in the category of healthy fitness zone. For body mass index, 55% scored in healthy fitness zone, 25% ni-some risk, and 10% each for ni-high risk and very lean. For push-up test and curl-up test, 80% and 65% scored in the healthy fitness zone while the remaining 20% and 35% respectively scored in the not healthy fitness zone. For flexibility, 75% of them scored in healthy fitness zone and 25% scored in not healthy fitness zone.Conclusions: The physical fitness level in these young football players is mostly in healthy fitness zone. [AMJ.2015;2(1):226–30]